2017
DOI: 10.3389/fendo.2017.00008
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Hepatic CEACAM1: A Unifying Mechanism Linking Insulin Resistance to Obesity and Non-Alcoholic Fatty Liver Disease

Abstract: The pathogenesis of human non-alcoholic fatty liver disease (NAFLD) remains unclear, in particular in the context of its relationship to insulin resistance and visceral obesity. Work on the carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) in mice has resolved some of the related questions. CEACAM1 promotes insulin clearance by enhancing the rate of uptake of the insulin-receptor complex. It also mediates a negative acute effect of insulin on fatty acid synthase activity. This positions CEACA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 73 publications
0
37
0
1
Order By: Relevance
“…Consistent with the predominant expression of the carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) in the liver [5], we have shown that CEACAM1 provides a post-receptor mechanistic underpinning of how impaired insulin clearance causes chronic hyperinsulinaemia [68]. Upon its phosphorylation by the insulin receptor [9], CEACAM1, a plasma membrane glycoprotein, increases the rate of receptor-mediated insulin uptake into the hepatocyte and its targeting to the degradation pathways by taking part in the insulin receptor endocytosis complex [10].…”
Section: Introductionmentioning
confidence: 74%
“…Consistent with the predominant expression of the carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) in the liver [5], we have shown that CEACAM1 provides a post-receptor mechanistic underpinning of how impaired insulin clearance causes chronic hyperinsulinaemia [68]. Upon its phosphorylation by the insulin receptor [9], CEACAM1, a plasma membrane glycoprotein, increases the rate of receptor-mediated insulin uptake into the hepatocyte and its targeting to the degradation pathways by taking part in the insulin receptor endocytosis complex [10].…”
Section: Introductionmentioning
confidence: 74%
“…As a result of the specific insulin-degrading enzyme, insulin degradation begins right before the acidification. In addition, enzyme CEACAM1 promotes insulin clearance by enhancing the rate of uptake of the insulin-receptor complex (29). Dissociated insulin is degraded in endosomes, translocated to cytosol and degraded there, or delivered to other subcellular compartments, such as peroxisomes (28).…”
Section: Discussionmentioning
confidence: 99%
“…29 Recently, enzyme CEACAM1 has been shown to promote the rate of uptake of the insulin-receptor complex. 30 IDE and/or CEACAM1 expression might be specifically reduced, inactivated or genetically altered in AAs, and possibly in HAs, because of genetic inheritance. Inactivation of CEACAM1 has been related to hyperinsulinaemia, insulin resistance, dyslipidaemia and visceral adiposity in transgenic mice 31 through downregulation of insulin receptors and increased hepatic lipogenesis.…”
Section: Discussionmentioning
confidence: 99%